Monk-artist hierodeacon Afoniy (Vishnyakov). Materials for a biography - Игорь Гарькавый (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
85 years ago, on March 17, 1938, on the territory of the Butovo special zone of the NKVD, a large group of christians was shot - 11 people from a secret monastic community that existed in the city of Sergiev Posad (since 1930 - Zagorsk) in the 20-30s. XX century. One of them was Hierodeacon Afoniy (in the world - Vishnyakov Alexander Egorovich, 1870-1938), an artist, a master of lacquer painting, who played an important role in the preservation and development of the traditions of folk lacquer painting in Soviet times. He came from a family of peasant painters, the creators of the Zhostovo tray craft. From 1892 he was a monk, later a hierodeacon of the Trinity-Sergius Lavra, and for some time a subdeacon of St. Patriarch Tikhon. An active participant in the secret monastic life in the city of Sergiev Posad (since 1930, Zagorsk) in the 20s - mid-30s. XX century. The article makes an attempt on the basis of newly studied documents, primarily the archival and investigative case of a group of believers, in which Fr. Afoniy, and documents of personal origin show the circumstances of the life path, arrest and execution of an outstanding monk-artist. A significant part of the documents is introduced into scientific circulation for the first time.